Role of fine needle aspiration cytology (FNAC) in head and neck neoplasms with histopathological correlation - Junu Devi; Kunja Lai Talukdar (Wolters Kluwer Medknow Publications, 2015)
Background : Fine needle aspiration cytology is a simple, quick,inexpensive and minimally invasive technique used to diagnose head and neck neoplasms commonly originated from cervical lymph node, thyroid, parotid and other salivary glands. In this study a correlation was done between cytology and histopathology whenever surgical specimens were available. Aim : To assess the frequency of various benign and malignant neoplasms in different age groups and to evaluate the sensitivity, specificity of fine needle aspiration cytology(FNAC) in head and neck neoplasms. Materials and method : The study was conducted between September 2011 to August 2013 and total 249 cases of head and neck neoplasms were analysed. Patients between 1 to 80 years were included in the study. Fine needle aspiration cytology (FNAC) diagnosis was correlated with histopathology whenever possible. Results: Out of 249 head and neck neoplasms 55.42% were from lymph node, 19.28% were from salivary gland,14.86% were from thyroid gland,1.20% were nasal mass, 9.24% from other sites (skin and soft tissue).M:F was 1.4:1. Most commonly affected age group was 51-60years. Metastatic squamous cell carcinoma was most commonly encountered neoplastic lesion. Overall sensitivity, specificity of fine needle aspiration cytology(FNAC) were 97.92% and 91.67% respectively. Conclusion : Fine needle aspiration cytology is a highly sensitive, specific and has a definite role in diagnosing most of the head and neck neoplasms.